Impacts of the COVID-19 pandemic on access to healthcare among people with disabilities: Evidence from six low- and middle-income countries - Hunt, Xanthe; Hameed, Shaffa; Tetali, Shailaja; Ngoc, Luong Anh; Ganle, John; Huq, Lopita; Shakespeare, Tom; Smythe, Tracey; Ilkkursun, Zeynep; Kuper, Hannah; Acarturk, Ceren; Kannuri, Nanda Kishore; et al. (BMC, 2024)
This article was published in The International Journal for Equity in Health [©2023 Rights managed by BMC] and the definite version is available at: https://doi.org/10.1186/s12939-023-01989-1 The Article's website is at: https://equityhealthj.biomedcentral.com/articles/10.1186/s12939-023-01989-1